101k views
4 votes
(Ight ima need some help!! ) solve the following equation (2x + 3) (3x + 2) − (3x + 2) (2x− 3) = 0. solve for x and show work

(2x + 3) (3x + 2) − (3x + 2) (2x− 3) = 0

1 Answer

2 votes

Answer:

x =
-(2)/(3)

Explanation:

I used the FOIL method

[(2x + 3) (3x + 2)] − [(3x + 2) (2x− 3)] = 0


(6x^(2) +4x+9x+6) - (6x^(2) -9x+4x-6)=0


(6x^(2) +13x+6) - (6x^(2) -5x-6)=0


(6x^(2) +13x+6) - 6x^(2) +5x+6=0

combine like terms


6x^(2) -6x^(2) = 0


13x+5x=18x


6+6=12

so,
18x +12 = 0

subtract 12 on both sides


18x=-12

divide by 18 to isolate x


x=-(12)/(18)

and simplifies to


x=-(2)/(3)

User Gabbler
by
4.8k points